THE FUTURE OF SURROGACY LAW: CAN EXISTING FRAMEWORKS ADAPT TO THE CHALLENGES OF ARTIFICIAL INTELLIGENCE? - Kaur, Harpreet; Negi, Monika; Srivastava, Deepak Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The advent of artificial intelligence (AI) in healthcare presents significant opportunities and challenges for surrogacy law. This paper examines how existing legal frameworks can adapt to the integration of AI in surrogacy, addressing potential legal, ethical, and practical implications. Current surrogacy laws, often rigid and jurisdiction-specific, may be ill-equipped to manage the complexities introduced by AI technologies, such as enhanced matching processes, surrogate health monitoring, and predictive analytics for pregnancy outcomes. Key challenges include privacy concerns, data security, and algorithmic bias, which necessitate robust legal and ethical oversight. The rights and responsibilities of intended parents, surrogates, and offspring must be re-evaluated in light of AI’s role in the surrogacy process. This paper proposes a flexible, technology-neutral regulatory framework to ensure surrogacy laws remain relevant and effective amidst rapid AI advancements. The framework emphasizes transparency, accountability, and ethical standards in AI deployment, aiming to protect all parties involved. By exploring the intersection of AI and surrogacy law, this study contributes to the broader discourse on legal adaptation to emerging technologies, highlighting the need for dynamic legal systems capable of evolving with technological progress.